2022
DOI: 10.3390/brainsci12010073
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from ERP and Eye Movements as Markers of Language Dysfunction in Dyslexia

Abstract: Developmental dyslexia is a complex reading disorder involving genetic and environmental factors. After more than a century of research, its etiology remains debated. Two hypotheses are often put forward by scholars to account for the causes of dyslexia. The most common one, the linguistic hypothesis, postulates that dyslexia is due to poor phonological awareness. The alternative hypothesis considers that dyslexia is caused by visual-attentional deficits and abnormal eye movement patterns. This article reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 81 publications
(145 reference statements)
1
19
0
Order By: Relevance
“…Sensory deficits in perception and discrimination of the phonological characteristics of stimuli are observed in different languages, being these deficits considered universal ( Goswami et al, 2011 ). Studies with different languages have shown changes in the N170 component (for review, see Premeti et al, 2022 ), so this deficit may be independent of linguistic regularity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensory deficits in perception and discrimination of the phonological characteristics of stimuli are observed in different languages, being these deficits considered universal ( Goswami et al, 2011 ). Studies with different languages have shown changes in the N170 component (for review, see Premeti et al, 2022 ), so this deficit may be independent of linguistic regularity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different languages show mixed results regarding differences between dyslexic and good readers. The inconsistency in the results of this component may be related to several factors such as the task, type of stimulus, age of the participants, or reading difficulty ( Premeti et al, 2022 ). Furthermore, since the N400 component is related to grapheme-phoneme and lexical-semantic and orthographic conversion processes, linguistic regularity can influence the mechanisms of linguistic information processing by dyslexic readers and good readers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have expanded the analysis of acoustic processing to visual discrimination tasks (Premeti et al, 2022;Schulte-Korne & Bruder, 2010). These experiments have revealed that deviations in the ERP signal, about 200 ms after stimulus onset, correlate with visual-orthographic processing and occur over the left occipital-temporal cortex (Maurer & McCandliss, 2008;Michel et al, 2004;Rossion et al, 2002;Tarkiainen et al, 1999).…”
Section: Neurophysiological Assessments Of Reading Abilitymentioning
confidence: 99%
“…During reading, control of eye movements is needed to coordinate both eyes (binocular coordination) in the correct direction of reading horizontally (from left to right in western writing systems) and vertically to start a new line. Eye movement patterns include a series of fixations (i.e., the maintenance of the gaze on a definite location to extract information) and saccades (i.e., shifts of the gaze between fixations that direct the eyes onto the next target to be fixated) (see review in [ 17 ]). Important findings show that the amount of information extracted during a single eye fixation during reading is tightly linked to reading ability development [ 18 ].…”
Section: Introductionmentioning
confidence: 99%